IDENTIFIKASI WISATA EDUKASI DI ASIA FARM PEKANBARU - Putri, Syifa Syauqiah; ', Etika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Tourism is one of the sectors that continues to grow and plays an important role in improving the economy and community education. Asia Farm Pekanbaru is present as one of the attractions that carries the concept of education with the nuances of animal husbandry and agriculture as well as interactive activities. This research aims to find out the identification of educational tourism in Asia Farm Pekanbaru and the obstacles faced by the management in its development. The method used is qualitative with data collection techniques through observation, interviews with key informants, and documentation. Interviews were conducted with managers, tour guides, and several tourists. The results showed that Asia Farm Pekanbaru offers various educational rides targeting children and families, such as animal feeding activities and an introduction to agriculture. Tour guides play an important role in assisting and delivering information to visitors in an interactive manner. The challenge faced by managers is how to maintain the attractiveness of tourism so that it remains in demand and is able to compete with other attractions. For this reason, the manager continues to strive to present new innovations in the future. The conclusion of this research is that Asia Farm Pekanbaru has realized quite diverse educational tourism, but sustainable efforts are still needed to maintain its attractiveness and sustainability. Keywords : Tourism, Educational Tourism, Asia Farm Pekanbaru.